The Danish problem - Barry Eichengreen (Danmarks Nationalbank, 2023)
Specialists in international finance have long been impressed by the fragility of currency pegs. Yet Danmarks Nationalbank has been able to maintain the krone's peg to the euro since the euro came into existence in 1999, and the krone's peg to the Deutschmark and SDR for 17 years before that. This paper considers a series of hypotheses that may help to account for the exceptional nature of this case. None of these explanations is entirely satisfactory, but collectively they go some way toward explaining the Danish exception.
Keywords: F3; F31; 330; Exchange rates; Currency peg